Guinea : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The report gives an assessment on the bauxite and aluminium industry of Guinea. The study assesses the performance, structure, and prospects of the industry as well as transparency and governance issues. The report also show the IMF's estimates on Guinea's social, demographic, economic, and financial indicators, GDP at current and at constant 1996 prices; financial operations of the central government, 2000-06, central government revenue and expenditure during 2000-06, summary accounts of the Central Bank as well as deposit money banks, structure of interest rates, financial soundness indicators of the banking sector, et cetera.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet